Violência Escolar na Perspectiva de Diretores: teoria versus prática - Beatris Cristina Possato Gianei (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article shows to the reader the summary of a research realized in 2000 and 2001, with five directors of the Fundamental Public Teaching of Rio Claro. Realized interviews of what to extracted informations concernings at representations of the directors with relation at violence and at actions adopted in the schools of these persons, to calm down the problematic. The analysis of the informations conducted to knowledge of a precarious situation in the selected schools, where the pratic of the exclusion is very employed yet.